The Reliability and Validity of “Dokuz Eylül University Meniere’s Disease Disability Scale” - Mutlu, Başak (J Int Adv Otol, 2018)
OBJECTIVE: Ménière’s Disease (MD) is a chronic, non-life threatening inner ear disease, with attacks of disabling vertigo, progressive hearing loss, and tinnitus as the major symptoms. All three symptoms, separately or in combination, cause great distress and have a considerable impact on the quality of life of the patients. The aims of this study were to develop a disease-specific quality of life survey for patients with MD and to analyze the relationships between the audiovestibular findings and the survey. MATERIALS AND METHODS: Following Ear-Nose-Throat examination and audiovestibular tests, the Dokuz Eylül University Meniere’s Disease Disability Scale (DEU-MDDS) and Turkish version of the Dizziness Handicap Inventory (DHI-T) were administered to 93 patients with definite MD. Reliability and validity analyses of the scale were performed. RESULTS: There were 45 (48.4%) male and 48 (51.6%) female patients and the mean age was 48.9±12.1 years. Cronbach’s alpha was 0.92 and intraclass correlation coefficients of the DEU-MMDS were significant (p<0.001). Results of the Goodness of Fit Statistics showed that the expression levels of the items were high and the correlation coefficients of each item with the scale were sufficient. There was a statistically significant correlation between DHI-T scores and MDDS. DEU-MDDS was not related to the vestibular tests, age or gender (p>0.05). CONCLUSION: The MDDS is a valid and reliable scale as a disease-specific quality of life questionnaire for patients with MD.